Examining a change in the properties of coarse wool fiber under the influence of electrical discharge treatment - Asaulyuk, Tatyana; Semeshko, Olga; Saribyekova, Yulia; Kunik, Aleksandra; Myasnykov, Sergey (Eastern-European Journal of Enterprise Technologies, 2017)
Modification of coarse wool fibre is a basic condition for improving quality of the manufactured woolen textile products while reducing their cost. Traditional methods of modification of wool are expensive, that is why the implementation of these methods into existing technological modes is not always economically justified. The obtained effect of modification is often associated with undesirable damage of protein structure of fiber. A solution to this problem is the application of electric discharge treatment, accompanied by the emergence of electric discharge non-linear bulk cavitation. It is shown that the influence of electrohydrolic shock and products of water cleavage on wool does not cause profound destruction of keratin, in contrast to enzymatic and plasmochemical methods of treatment. Based on the performed experimental studies, it was determined that during electric discharge treatment of coarse wool there occurs the compaction of fiber cuticles and a change in supramolecular structure of keratin. This fact predetermines a decrease in felting ability of wool fibre, an increase in sorption properties, as well as in resistance to hydrolysis and influence of oxidants and reductants. It was established that the application of electric discharge treatment as a method of coarse wool modification would contribute to a decrease in shrinking and improvement of optimized dyeing of woolen textile material. Thus, the proposed technology of wool improvement will make it possible to use less expensive raw materials for the production of textile materials for different purposes.